Congenital ptosis repair—surgical, cosmetic, and functional outcome: a report of 162 cases - Skaat, Alon; Fabian, Didi; Spierer, Abraham; Rosen, Nachum; Rosner, Mordechai; Ben Simon, Guy J. (Canadian journal of ophthalmology, 2013)
To evaluate the surgical and functional outcome of congenital ptosis repair and the anisometropic changes after surgical repair of ptosis to determine the potential contribution of anisometropia to the development of refractive amblyopia. The clinical records of 162 children with congenital ptosis that had been surgically repaired between 1995 and 2006 at the Goldschleger Eye Institute were reviewed and analyzed for functional and cosmetic outcome, visual acuity status, and presence of amblyopia. A total of 162 patients (mean age, 10 months) underwent surgical ptosis repair, of whom 120 (74%) had unilateral and 42 (26%) had bilateral ptosis. The surgeries were levator resection (47.5%), frontalis suspension (46.3%), and Fasanella-Servat (7.4%). Good functional and cosmetic outcomes were achieved in 130 (80.2%) patients, with unilateral cases showing more postoperative asymmetry. The reoperation rate was 10.4% (8/77) for levator resection, 29.3% (22/75) for frontalis suspension, and 20% (2/10) for Fasanella-Servat. There were no significant differences in visual acuity, spherical equivalent, or mean cylinder at 90° between the ptotic eyes before and after surgery (P = 0.33, P = 0.83, and P = 0.65, respectively), and compared with the sound eyes (P = 0.66, P = 0.78, and P = 0.08, respectively). The mean astigmatism correction by vector analysis after ptosis surgery was 1.1±0.68 D. Congenital ptosis repair yields good functional and cosmetic outcome, although the reoperation rate is relatively high (19.8%). Congenital unilateral ptosis was not associated with any differences in anisometropia or astigmatism between the ptotic and sound eye. Évaluation des résultats chirurgicaux et fonctionnels du relèvement de la ptose congénitale et des modifications anisométropiques après le relèvement chirurgical de la ptose, afin de déterminer les possibilités de contribution de l'anisométropie au développement de l'amblyopie réfractive. Révision et analyse des dossiers cliniques de 162 enfants atteints de ptose congénitale relevée chirurgicalement entre 1995 et 2006 au Goldschleger Eye Institute, quant aux résultats fonctionnels et cosmétiques, au degré d'acuité visuelle et à la présence de l'amblyopie. En tout, 162 patients (âgés de 10 mois en moyenne) ont subi une chirurgie réparatrice de la ptose. Parmi eux, 120 (74 %) avaient une ptose unilatérale et 42 (26 %), une ptose bilatérale. Les chirurgies furent la résection des élévateurs (47,5 %), la suspension frontale (46,3 %) et la Fasanella-Servat (7,4 %). De bons résultats fonctionnels et cosmétiques ont été atteints chez 130 patients (80,2 %), avec des cas unilatéraux montrant plus d'asymétrie postopératoire. Les taux de réopération étaient de 10,4 % (8/77) des résections des élévateurs, 29,3 % (22/75) des suspensions frontales et 20 % (2/10) des Fasanella-Servat. Il n'y avait pas de différence significative d'acuité visuelle, d'équivalence sphérique ou de moyenne cylindrique de 90° entre les yeux ptotiques avant et après la chirurgie (P=0,33, P=0,83 et P=0,65 respectivement), et à comparer aux yeux sains (P= 0.66, P=0.78, et P=0.08, respectivement). La moyenne de correction de l'astigmatisme par analyse vectorielle après la chirurgie de la ptose était de 1,1 ± 0,68 dioptries. La réparation de la ptose congénitale donne de bons résultats fonctionnels et cosmétiques, bien que le taux de réopération soit relativement élevé (19,8 %). La ptose congénitale unilatérale n'était pas ass/ociée avec toute différence d'anisométropie ou d'astigmatisme entre l'œil ptosique et l'œil sain.